The urine output definition of acute kidney injury is too liberal - Md Ralib, Azrina; Pickering, John W.; Shaw, Geoffrey M.; Endre, Zoltan H. (Critical Care Forum, 2013)
INTRODUCTION: The urine output criterion of 0.5 ml/kg/h for 6-hours for acute kidney injury, (AKI) has not been prospectively validated. Urine output criteria for AKI (AKIUO) as predictors of in-hospital mortality or dialysis need were compared. METHODS: All admissions to a general ICU were prospectively screened for 12 months and hourly urine output analysed in collection intervals between 1 and 12 hours. Prediction of the composite of mortality or dialysis by urine output was analysed in increments of 0.1 ml/kg/h from 0.1 to 1 ml/kg/h and the optimal threshold for each collection interval determined. AKICr was defined as an increase in plasma creatinine of [greater than or equal to]26.5 mol/l within 48 hours or [greater than or equal to]50% from baseline. RESULTS: Of 725 admissions, 72% had either AKICr or AKIUO or both. AKIUO (33.7%) alone was more frequent than AKICr (11.0%) alone (P<0.0001). A 6-hour urine output collection threshold of 0.3 ml/kg/h was associated with a step increase in in-hospital mortality or dialysis (from 10% above to 30% less than 0.3 ml/kg/h). Hazard Ratios for in-hospital and one-year mortality were 2.25 (1.40 to 3.61) and 2.15 (1.47 to 3.15) respectively after adjustment for age, body weight, severity of illness, fluid balance, and vasopressor use. In contrast, after adjustment AKIUO was not associated with in-hospital or 1-year mortality. The optimal urine output threshold was linearly related to duration of urine collection (r2=0.93). CONCLUSIONS: A 6-hour urine output threshold of 0.3 ml/kg/h best associated with mortality and dialysis and was independently predictive of both hospital and 1-year mortality. This suggests that the current AKI urine output definition is too liberally defined. Shorter urine collection intervals may be used to define AKI using lower urine output thresholds.